2010
DOI: 10.1016/j.wem.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

End-Tidal Partial Pressure of Carbon Dioxide and Acute Mountain Sickness in the First 24 Hours Upon Ascent to Cusco Peru (3326 meters)

Abstract: The most important finding of this study is that Petco(2) upon ascent was found to have a more significant effect than Spo(2) on a subject's ultimate ESQ score. This study demonstrates that those individuals with a brisk ventilatory response upon ascent to moderate altitude, as measured by Petco(2), did not develop AMS, whereas a blunted ventilatory response, as reflected in the highest Petco(2), was related to the subsequent development of AMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Up to now, several studies have been conducted focusing on physiological aspects and mechanisms of headache as the major symptom of AMS. Nowadays, AMS is defined as altitude-induced headache in addition to at least one typical symptom such as anorexia, nausea, vomiting, insomnia, dizziness and fatigue [ 1 , 12 , 15 17 ] . Altitude above 5500m leads to severe hypoxemia, hypocapnia and alkalosis in addition to progressive impairment of physiological function of individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, several studies have been conducted focusing on physiological aspects and mechanisms of headache as the major symptom of AMS. Nowadays, AMS is defined as altitude-induced headache in addition to at least one typical symptom such as anorexia, nausea, vomiting, insomnia, dizziness and fatigue [ 1 , 12 , 15 17 ] . Altitude above 5500m leads to severe hypoxemia, hypocapnia and alkalosis in addition to progressive impairment of physiological function of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Headache starts as early as 8-24 hours after arrival at 2000m but often is most felt after 48-72 hours [ 15 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated variable results with end tidal carbon dioxide and altitude. Douglas et al demonstrated an increase in ETCO 2 with higher altitude in Cusco, Peru for a 2 day climb [ 6 ]. However, over 30% of subjects were lost to follow up in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Partial pressure of oxygen (PaO 2 ) 5 , the partial pressure of carbon dioxide (PaCO 2 ) 6 , the saturation of oxygen (SaO 2 ) 7 , 8 , arterial oxygen content (CaO 2 ) 9 , oxygen tension at 50% haemoglobin saturation (P50) 10 and haemoglobin 11 were thought to be hypoxia-sensitive and evidenced either as independent predictors or factors related to the subsequent development of AMS; however, speculation remains regarding their importance in the prediction of AMS. To date, studies concerning the predictive value of blood gas testing are rather limited.…”
Section: Introductionmentioning
confidence: 99%